Reestruturação patrimonial de empresas no Brasil e na Argentina (1990-1999) - Knorst, Aline Solange (2007)
This work presents the patrimonial restructuring process occurrence in the economies of Brazil and Argentina in 1990s. In this period, the changes in the international economic environment and national environments had provided new chances of businesses in the whole world. It enters the external factors associates to the growth of the merger and acquisition processes in these countries is detached the markets saturation of some developed countries, the world-wide financial liquidity, the changes in regulation structure of developed countries, the regional integration process and the world-wide productive reorganization. In relation to the internal factors, the privatization processes, the commercial opening, the financial liberalization and the regulation/deregulation of the economy are detached. In Brazil, the merger and acquisition processes had been carried through in its majority for transnational companies, who already withheld significant parcel of the market, evidencing the economy process of denationalization. In Argentina, the result of patrimonial reorganization process in the economy was to the magnifying of the participation of foreign companies and the strengthening of great national economic groups. In each country, Brazil and Argentina, the cycle of M&As revealed entailed to the international movement. However, the growth of the economies participation in this movement occurred at different moments. In this aspect, the M&As had been bigger relevance at the beginning of the 1990 for Argentina, while in Brazil, had grown from the half of the period.